1998
DOI: 10.1002/(sici)1097-4636(19980305)39:3<458::aid-jbm16>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Positively charged dextran resin inhibits trabecular bone repair in the rabbit tibial physis

Abstract: Because exposure to positively charged dextran resin (PCDR) inhibits the growth of cultured rat and human bone cells, we tested the hypothesis that PCDR might inhibit bone repair in vivo. Central physeal defects were created by drilling 3.0-mm holes from the proximal tibial plateau into the metaphysis. The defects in left tibiae were packed with neutral resin (control); those in right tibiae were filled with PCDR. At the end of the 1st, 2nd, 3rd, and 10th postoperative weeks, the outcomes were quantitated by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In all the groups, no phagocytic reaction with multinucleated giant cells was found in the gap areas 7 days after implantation. Because in almost all reports of histologic investigations concerning the charged surfaces of polymer beads, the inflammatory reaction was dominant on day 7, regardless of the polarity and the magnitude of the charges, 4,6,17,18 it is difficult to compare the present results of the charged HAp surfaces with previous studies on charged polymers. At 14 days, the newly formed bone layers directly bonding to the N-surfaces had thickened 2-3 times compared with their thickness on day 7 [ Fig.…”
Section: Cell Reactions To Charged Hap Ceramic Surfacesmentioning
confidence: 68%
See 1 more Smart Citation
“…In all the groups, no phagocytic reaction with multinucleated giant cells was found in the gap areas 7 days after implantation. Because in almost all reports of histologic investigations concerning the charged surfaces of polymer beads, the inflammatory reaction was dominant on day 7, regardless of the polarity and the magnitude of the charges, 4,6,17,18 it is difficult to compare the present results of the charged HAp surfaces with previous studies on charged polymers. At 14 days, the newly formed bone layers directly bonding to the N-surfaces had thickened 2-3 times compared with their thickness on day 7 [ Fig.…”
Section: Cell Reactions To Charged Hap Ceramic Surfacesmentioning
confidence: 68%
“…Cobos et al reported, based on implantation tests using rabbit physis for 1 to 10 weeks, that positively charged dextran resin inhibits trabecular bone repair. 17 Cherico et al studied the effect of electrically charged GTAM on bone formation using rabbit calvarial defects and reported that negatively charged GTAM membranes accelerate and maintain bone neogenesis for terms of 5 days-20 weeks and that positively charged membranes show the lowest new bone formation. 18 These suppressive effects of the positively charged polymer surfaces on bone formation are contrary to the present results.…”
Section: Bone Formation In the Vicinity Of The Positively Charged Surmentioning
confidence: 99%
“…The primary interaction between a biomaterial and the surrounding bone involves the outermost molecular layers of the implant [2]. Thus, the surface micro-roughness [3,4], surface energy [5,6], and surface charge [7,8] of the biomaterial play important roles in influencing cellular response.…”
Section: Introductionmentioning
confidence: 99%